Buddleoside-Rich Chrysanthemum indicum L. Extract has a Beneficial Effect on Metabolic Hypertensive Rats by Inhibiting the Enteric-Origin LPS/TLR4 Pathway - Wang, Ya-Jun; Su, Jie; Yu, Jing-Jing; Yan, Mei-Qiu; Shi, Meng-Lin; Huang, Qi-Di; Li, Bo; Wu, Wen-Yan; Xia, Rong-Shuang; Li, Si-Fan; Chen, Su-Hong; Lv, Gui-Yuan (Frontiers in Pharmacology, 2021)
As the number of patients with metabolic hypertension (MH) is increasing, there is an essential require for global measures to prevent and treat MH. Flavonoids such as buddleoside (BUD) from Chrysanthemum indicum L. are the main pharmacological components of cardiovascular activities. Previous studies have suggested that the buddleoside-rich Chrysanthemum indicum L. extract (BUDE) can reduce blood pressure in spontaneously hypertensive rats (SHR). However, its effect on MH and how it works remains to be researched. In this study, it was observed that BUDE could lower blood pressure, improve dyslipidemia, and decrease the level of plasma LPS in MH rats. Moreover, BUDE improved intestinal flora and increased the expression of occludin and claudin-1 in the colon, and improved the pathological injury of the colon. Western bolt and qRT-PCR experiments showed that BUDE could down-regulate TLR4 and MyD88 protein and mRNA expression and inhibit phosphorylation of IKKβ, IκBα and NF-κB p65 in vessels of MH rats. These results showed that BUDE could regulate intestinal flora, improve intestinal barrier function, reduce the production and penetration of LPS, thereby inhibiting the vascular TLR4/MyD88 pathway, improving vascular endothelial function, and ultimately lowering blood pressure in MH rats. This study provides a new mechanism of BUDE against MH by inhibiting the enteric-origin LPS/TLR4 pathway.